Cover Feature: A Combined Sodium Intercalation and Copper Extrusion Mechanism in the Thiophosphate Family: CuCrP2S6 as Anode Material in Sodium‐Ion Batteries (ChemElectroChem 11/2022). Issue 11 (3rd May 2022) - van Dinter, Jonas; Grantz, David; Bitter, Alexander; Bensch, Wolfgang
Abstract : The Cover Feature illustrates the combined sodium intercalation and copper extrusion mechanism occurring during the discharge process of CuCrP2 S6 anodes in sodium‐ion batteries. Initially, Na + ions intercalate into the van der Waals gaps of CuCrP2 S6 and Cu + ions are expelled followed by reduction to elemental Cu. During this initial process the crystallinity of the host structure is mainly maintained, but an expansion of the interlayer space is observed. More information can be found in the Research Article by J. van Dinter et al .